(untitled) (Development Service Industry Management, 2024)
In the study, attention is updated to the problems of the development of entrepreneurial activity in the production sector of the national economy, namely in the woodworking industry. The purpose of the study is to improve the theoretical and methodological foundations and methodological and applied features of entrepreneurial activity in the woodworking industry of Ukraine. It has been established that business activities in the woodworking industry include logging, primary wood processing, furniture production, pulp and paper industry and other related industries. However, the woodworking industry is integrated into the national economy through various inter-industry linkages, providing raw materials for other industries such as construction, chemical industry, engineering, etc., and also depends on the supply of materials and machinery from other sectors. The specific characteristics of entrepreneurship in the woodworking industry have been identified, both directly in the organization and implementation of business, and in the mechanisms and tools of state support for the development of entrepreneurial activity. In particular, enterprises engaged in woodworking should take into account not only economic, but also environmental aspects of their activity. This includes rational and responsible management of forest resources, implementation of innovative processing methods and maximum reduction of negative impact on the environment. A balanced approach to the use of wood contributes not only to the maintenance of the ecological balance, but also opens the way for the sustainable development of the enterprise. Technological aspects in the woodworking industry should also be considered critically important, since this industry depends on the use of specialized equipment for effective wood processing.